DESIGNING PROTOTYPE OF A DUAL GAS AND SMOKE DETECTOR BASED ON ARDUINO UNO USING MQ-2 SENSOR - Fauzan Febriano; Zidni Ma'ruf; Naurah Talitha Andriani; Tri Baroto Seto; Rizky Amelia Putri (Jurnal Informatika dan Teknik Elektro Terapan, 2026)
The growing reliance on Liquefied Petroleum gas (LPG) as a major cooking gasoline in Indonesian households has significantly enhanced operational efficiency and monetary practicality in normal domestic activities. however, the giant utilization of LPG additionally elevates the ability risk of risky conditions, such as fuel leakage, smoke accumulation, and fireplace incidents. present day detection structures predominantly deal with identifying both gas leaks or smoke independently, thereby decreasing their capability to provide complete residential safety tracking. This study focuses on the design and implementation of an incorporated twin gas and smoke detection prototype utilizing the Arduino Uno microcontroller and MQ-2 sensor to supply real-time early warning signals underneath hazardous situations. The research adopted a prototype-oriented development method encompassing system design, hardware integration, software programming, and experimental testing. The developed prototype incorporated numerous hardware additives, including an Arduino Uno board, MQ-2 sensor, LED indicators, buzzer alarms, breadboard, jumper wires, and a USB strength deliver. The software system was programmed the usage of the Arduino IDE and the C/C++ programming language to continuously examine environmental conditions and robotically spark off warning signs whenever gasoline or smoke concentrations passed predefined thresholds. Experimental evaluation proven that the proposed system performed dependable detection performance with rapid reaction capability.